2002
DOI: 10.1038/sj.npp.1300114
|View full text |Cite
|
Sign up to set email alerts
|

Selective Antagonism at Dopamine D3 Receptors Enhances Monoaminergic and Cholinergic Neurotransmission in the Rat Anterior Cingulate Cortex

Abstract: Recent neuroanatomical and functional investigations focusing on dopamine (DA) D 3 receptors have suggested a potential role of this receptor in psychiatric diseases such as schizophrenia and drug dependence. In line with the key role of the prefrontal cortex in psychiatric disorders, the present study aimed at assessing the effects of the acute systemic administration of the selective DA D 3 receptor antagonist SB-277011-A on the in vivo extracellular levels of monoamines (DA, norepinephrine (NE), and seroton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 76 publications
(101 reference statements)
4
60
0
1
Order By: Relevance
“…In contrast, SB-277011-A does not modify basal DA neurotransmission in the NAc, but can reverse quineloraneinduced decreases in extracellular DA levels in the same brain area (Reavill et al, 2000). We have recently shown that the acute systemic administration of SB-277011-A can increase extracellular DA levels in the rat anterior cingulate cortex (ACg) (Lacroix et al, 2003). Interestingly, the projections from the ACg terminate more medially and extend further ventrally to include the core of the NAc (Ding et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SB-277011-A does not modify basal DA neurotransmission in the NAc, but can reverse quineloraneinduced decreases in extracellular DA levels in the same brain area (Reavill et al, 2000). We have recently shown that the acute systemic administration of SB-277011-A can increase extracellular DA levels in the rat anterior cingulate cortex (ACg) (Lacroix et al, 2003). Interestingly, the projections from the ACg terminate more medially and extend further ventrally to include the core of the NAc (Ding et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo brain microdialysis data indicate that administration of SB-277011-A (2.8 mg/kg po) reverses the decrease in extracellular DA levels produced by quinelorane (D 2 /D 3 agonist) in the NAc, but not the dorsal striatum, a regional selectivity consistent with the distribution of DA D 3 receptors in the rat brain [229]. A single ip administration of 10 mg/kg of SB-277011-A significantly increases extracellular levels of DA, norepinephrine (NE), and acetylcholine (ACh) in the anterior cingulate cortex in freely moving rats [160]. It should be pointed out that SB-277011-A does not produce a functional antagonism of D 2 receptors in vivo as, unlike D 2 receptor antagonists, its systemic administration in rats does not (1) elicit catalepsy at doses that exhibit anti-addiction action [229,295]; (2) produce a rightward shift in brain stimulation reward curve [229]; (3) increase plasma prolactin levels [295]; (4) inhibit spontaneous or stimulant-induced locomotion [295]; (5) antagonize the action of quinpirole in the dorsal striatum, a brain region with a high density of D 2 receptors [295]; (6) increase DA levels in the striatum [295]; and (7) increase cocaine self-administration under a schedule of continuous reinforcement ( [84,102,295]; see Section 7.4).…”
Section: Role Of Da D 3 Receptors In Drug Addiction: Studies With Mixmentioning
confidence: 91%
“…However, SB-277011-A does not appear to alter memory (as measured using a delayed nonmatched position test, D. Jones and J.J. Hagan, personal communication). Furthermore, acute administration of SB-277011-A significantly increases ACh levels in the anterior cingulate cortex [160] and reverses scopolamine-induced memory deficits as assessed by the threechoice point water labyrinth test [163]. Both of these effects would be expected to improve rather than to interfere with memory.…”
Section: Summary Of Effects Of Sb-277011-a On Addictive Drug Actionmentioning
confidence: 99%
“…30 min prior to testing for reinstatement. The doses of the drugs and the pretreatment times were chosen based upon the previously published pharmacokinetic and pharmacodynamic properties of the three D 3 compounds (Yuan et al, 1998;Pilla et al, 1999;Austin et al, 2001;Beardsley et al, 2001;Robarge et al, 2001;Aujla et al, 2002;Duarte et al, 2003;Garcia-Ladona and Cox, 2003;Heidbreder et al, 2005), our own previous studies (Vorel et al, 2002;Ashby et al, 2003;Campos et al, 2003Campos et al, , 2004Gilbert et al, 2003;Lacroix et al, 2003;Xi et al, 2003Xi et al, , 2004, and pilot studies carried out in preliminary phases of the present investigation.…”
Section: Cue-induced Reinstatement Of Drug-seeking Behaviormentioning
confidence: 99%